POLICY STRATEGY FOR THE DEVELOPMENT OF GURAMI FISH FARMING AREAS IN KEMRANJEN DISTRICT, BANYUMAS REGENCY - Frentina Murti Sujadi; Asro Nurhabib; Taufik Budhi Pramono (Universitas Mataram, 2025)
Gourami fish (Osphronemus goramy) is a freshwater commodity with high economic value and stable market demand, playing an important role in supporting community income and food security. Kemranjen Subdistrict, Banyumas Regency is known as a centre for gourami cultivation with great potential due to the availability of water resources, the experience of farmers, and government programme support. However, the development of this area still faces various obstacles such as technological limitations, fluctuations in feed prices, variations in the quality of cultivation management, environmental challenges and suboptimal digital marketing. These conditions require appropriate policy strategies to increase productivity and business sustainability. This research aims to formulate a strategy for developing the gurami farming area in Kemranjen Subdistrict through SWOT analysis to identify the strengths, weaknesses, opportunities, and threats that affect the development of the area. Primary data was collected through observation, interviews, and questionnaires to 40 respondents consisting of farmers, fisheries extension workers, village officials, and the Banyumas Regency Fisheries Service. IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) analyses were used to determine the position of the area development strategy. The results of the study show a value of (S-W) = +0.408 and (O-T) = +0.336, placing the area in Quadrant I (aggressive strategy), which is a condition where internal strengths can be optimally utilised to seize external opportunities. The priority strategies include the application of modern cultivation technology, strengthening digital marketing, increasing human resource capacity, and sustainable environmental management. The implementation of these strategies is expected to increase the competitiveness of the gurami cultivation area and support the improvement of the welfare of farmers in Kemranjen Sub-district.